Analisis Daya Saing Industri Pariwisata di Kabupaten Manokwari - Yustinus Mayai Kapitarauw; Dedy Riantoro; Sarce Babra Awom (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2022)
This study focuses on measuring the competitiveness of the tourism industry in Manokwari Regency by using eight main indicators as a measure of tourism competitiveness, namely, Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indictor (IDI), Environmnt Indicator (EI), Technology Advancement Indicator (TAI), Human Resources Indicator (HRI), Openness Indicator (OI) and Social Development Indicator (SDI). This study uses secondary data. The analytical method used in this study is the tourism competitiveness index with the Competitiveness Monitor method. The results of the analysis show that, the eight indicators show very high development, there is only one indicator that is very low where the indicator is the Social Development Indicator (SDI) of -1,7 which means that it shows low competitiveness where the value is less than 1, in addition to other than that other indicators show good or highcompetitiveness development where the value is greater than 1. Penelitian ini berfokus pada pengukuran Daya Saing industri Pariwisata di Kabupaten Manokwari dengan mengunakan delapan indikator utama sebagai pengukur daya saing pariwisata yaitu, Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Environtment Indicator (EI), Technology Advancement Indicator (TAI), Human Resources Indicator (HRI), Openess Indicator (OI) dan Social Development Indicator (SDI). Penelitian ini menggunakan data sekunder. Metode analisis yang digunakan dalam penelitian ini adalah indeks daya saing pariwisata dengan metode Competitiveness Monitor. Hasil analisis menunjukkan bahwa, kedelapan indikator menunjukan perkembangan sangat tinggi hanya terdapat satu indikator yang sangat rendah di mana indikator tersebut adalah Sosial Development Indicator (SDI) sebesar -1,7 yang artinya menunjukkan kemampuan daya saing yang rendah dimana nilanya lebih kecil dari 1, selain dari pada itu indikator-indikator lain menunjukan perkembangan daya saing yang baik atau tinggi dimana nilainya adalah lebih besar dari 1